APPLICATIONS OF QUASI-STATIC METHOD IN STATIC FAILURE SIMULATION FOR LARGE AIRCRAFT WINGBOX - YU Ming; LING XiaoTao; WANG QianPing (Jixie qiangdu)
The strength problems of large-aircraft wingbox is complex.Studying the bearing characteristics of wingbox,plays an important role in wing structure refined design,weight optimization and development cost saving.Based on the explicit time integration,this paper simulated the static loading process of typical wingbox section until failure in quasi-static limits,while taking the material nonlinearity and damage characteristics into consideration.Both the strain distribution and the strength prediction agree well with the experimental results.The study provides a reference for evaluating the ultimate strength of aircraft assembly.